CRUDE BACTERIOCIN EXTRACT EFFECT ON THE MICROBIOLOGICAL AND SENSORIAL CHARACTERISTICS OF SOLOMO REDONDO (Longissimus dorsi) VACUUM-PACKAGING - VÁSQUEZ, Sandra M.; SUÁREZ M., Héctor; MONTOYA C., Olga I. (Vitae, 2009)
The application of crude bacteriocins extract (CBE) produced by Lactobacillus plantarum LPBM10 is tested on the microbiological and sensory characteristics of rib filets (Longissimus dorsi) vacuum packing for 31 days storage at 3°C. As parameters of meat quality through time microbiology analysis, pH, cutting force, weight loss and sensorial are made. Significant differences are found in psychrotrophic counts in the fifth day storage, being better the treatment with crude bacteriocin extract. Levels of fecal coliforms persistaround 1.5 UFC/g in meat samples with crude bacteriocins extract. Significant difference in every day storage (p<0.05) are observed and a germicide effect presents in the day 23 diminishing the recounts of these microorganisms in 1 cycle log. There are not statistic differences among treatments for mesophilic counts neither total coliforms, but in day 23 the crude extract is able to diminish the recounts in 0.9 cycle’s log. Variations of pH and weight loss present significant differences (p<0.05), due to maturation and vacuum packing, while cutting force diminishes during storage time without significant difference among treatments (p<0.05). Appearance, color and aroma diminish the acceptance value as storage time advances presenting statistical differences among treatments reaching better scores the lactic acid treatment. The treatments applied to meat decrease the counts of micro-organisms evaluated showing its antagonistic effect and increasing the meat safety.